Performa dan Profil Hematologi Itik Hibrida yang Disuplementasi Larutan Tanaman Pegagan (Centella asiatica (Linn) urban) dan Daun Kersen (Muntingia calabura L) Melalui Air Minum: Performance and Blood Hematology of Hybrid Ducks Supplemented with Pegagan Plant (Centella asiatica (Linn) urban) and Cherry Leaves (Muntingia calabura L) Solution Through Drinking Water - Ningsih, Sekar Maulidya; Suci, Dwi Margi; Hermana, Widya (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
The study aims to evaluate the effect of giving Cherry leaves and Centella asiatica herbs to drinking water on the production performance and hematology profile of hybrid ducks starter. This study used 96 hybrid ducks aged 1 to 14 days, which were fed commercial feed (protein 21-23%) with 3 treatment groups and 4 replications. A completely randomized design was used in this research. The treatments were: P0 (control), P1 (2 ml of Cherry leaves + 3 ml of Centella asiatica solution), and P2 (4 ml of Cherry leaves + 6 ml of Centella asiatica solution). A completely randomized design was used in this experiment, and data were analyzed using analysis of variance (ANOVA) and Duncan's Multiple Range Test. The results of the study showed that supplementation of Centella asiatica and Cherry leaves solutions at doses of 5 ml and 10 ml in drinking water in 2-week-old hybrid ducks significantly (p<0.05) reduced body weight gain but did not affect feed consumption and FCR. All treatments showed no difference in hematology profiles and leukocyte differentiation compared to controls. Supplementation of Centella asiatica and cherry leaf solutions in the drinking water did not cause any negative effects on production performance and hematology profile of the hybrid ducks.